Anxiety and depression after thoracic aortic surgery or coronary artery bypass. (February 2013) - Okamoto, Yuko; Motomura, Noboru; Murashima, Sachiyo; Takamoto, Shinichi
Background: although the outcome of thoracic aortic surgery has improved remarkably, mortality remains high, and mental distress is often present. Psychological outcomes of coronary artery disease have been increasingly researched but few studies have been conducted in thoracic aortic surgery patients. Objective: to compare the psychological outcomes of patients undergoing thoracic aortic surgery with those of patients undergoing coronary artery bypass grafting. Methods: a questionnaire was mailed to 190 patients who underwent thoracic aortic surgery or coronary artery bypass, at 1–5 years postoperatively. Psychological outcomes were assessed using the hospital anxiety and depression scale. Results: 128 patients responded; 49 had aortic surgery and 79 had coronary artery bypass. The incidence of borderline or significant anxiety was 14% in thoracic aortic surgery patients and 16% in coronary bypass patients; depression was present in 28% and 20%, respectively. Psychological outcome scores in the 2 groups did not differ significantly. Emergency surgery was associated with depression after aortic surgery, and symptoms such as chest pain and fatigue were associated with both anxiety and depression after coronary artery bypass. Conclusions: some psychological problems remain in the midterm following thoracic aortic surgery. While we expected a more psychologically compromised outcome in the thoracic aortic surgery group, psychological outcomes were quite similar to those in coronary artery bypass patients. The similarity of the profiles of both groups suggests that thoracic aortic surgery patients have a parallel course of midterm psychological improvement following surgery.